2018
DOI: 10.1051/0004-6361/201731536
|View full text |Cite
|
Sign up to set email alerts
|

Stellar parameters of Be stars observed with X-shooter

Abstract: Aims. The X-shooter archive of several thousand telluric standard star spectra was skimmed for Be and Be shell stars to derive the stellar fundamental parameters and statistical properties, in particular for the less investigated late-type Be stars and the extension of the Be phenomenon into early A stars.Methods. An adapted version of the BCD method is used, using the Balmer discontinuity parameters to determine effective temperature and surface gravity. This method is optimally suited for late B stars. The p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…However, recent results based on space photometry suggest that (part of) this phenomenon may be rather due to differences in amplitude than outburst activity. Shokry et al (2018) confirm that late-type Be stars are generally less variable than their early-type counterparts. In order to bring out the eclipses more clearly, the phase plot has been based on only part of the ASAS-3 data, as indicated below the abscissa.…”
Section: Discussionsupporting
confidence: 55%
“…However, recent results based on space photometry suggest that (part of) this phenomenon may be rather due to differences in amplitude than outburst activity. Shokry et al (2018) confirm that late-type Be stars are generally less variable than their early-type counterparts. In order to bring out the eclipses more clearly, the phase plot has been based on only part of the ASAS-3 data, as indicated below the abscissa.…”
Section: Discussionsupporting
confidence: 55%
“…This suggests an MK type closer to B7 III. For B7 III and B8 III, the grid of stellar parameters calculated by Shokry et al (2018), which is based on Zorec et al (2009), is provided in Table 2. The derived parameter values are comparable to those compiled by White et al (2017) for the B-type stars in the Pleiades.…”
Section: Spectroscopymentioning
confidence: 99%
“…At the cool limit of the so-called Be phenomenon, spectroscopic evidence of a disk is often restricted to shell absorption lines. However, recent observations by Shokry et al (2018) have demonstrated that, with the help of high-quality spectral line profiles, weak Hα emission can be detected in many more late B-type stars than previously thought. The variability of their emission lines seems to be much slower and reach lower amplitudes than displayed by many early-type Be stars (Barnsley & Steele 2013).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The origins of these variations are disk formation and dissipation for the longer term variations (Okazaki, 1997;Haubois et al, 2012;Rímulo et al, 2018) and pulsations within the B star photosphere for the short ones (Baade, 2000;Huat et al, 2009). According to the results of photometric studies, earlier type Be stars are more likely variable (Hubert and Floquet, 1998;Labadie-Bartz et al, 2018;Shokry et al, 2018).…”
Section: Variations In the Observablesmentioning
confidence: 99%